Comparison of Anatomical and Indication-Based Diagnostic Reference Levels (DRLs) in Head CT Imaging: Implications for Radiation Dose Management - Benard Ohene-Botwe; Samuel Anim-Sampong; Robert Saizi (International Journal of Biomedical Imaging)
Conclusion:The study highlights that using anatomical DLP DRL values for specific indications in head CT scans can lead to underestimated or overestimated DLP values, making them less reliable for radiation management compared to indication-based DRLs. Therefore, it is imperative to promote the establishment and use of indication-based DRLs for more accurate dose management in CT imaging.